IMPLEMENTASI PENDIDIKAN KARAKTER BERDASARKAN NILAI-NILAI PANCASILA DI SMA NEGERI 1 CIBUNGBULANG - Rahmawati, Ima; Rustini, Titin; Lestari, Hana; Lestari, Fitri (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
The importance of character education in the era of globalization which increasingly requires character education that is guided by Pancasila. This research aims to find out what activities constitute the application of character education based on Pancasila values at SMA Negeri 1 Cibungbulang. The research method used is descriptive qualitative using interviews, observation and literature study. The results of this research explain that the implementation of character education based on Pancasila values at SMA Negeri 1 Cibungbulang can be seen from several existing activities such as congregational noon and asr prayers, joint dhuha prayers every Friday, routine flag ceremonies. every Monday, always implementing the 5S culture, the school can openly accept input, opinions, suggestions from the school community, from the use of school uniforms as well as in extracurricular activities at SMA Negeri 1 Cibungbulang